2015
DOI: 10.1007/s13197-015-1716-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel yoghurt based on date liquid sugar: physicochemical and sensory characterization

Abstract: The addition effect of date liquid sugar (DLS, 1-9 % v/v) to yoghurt milk on the physical (colour, firmness and syneresis), chemical (pH, total titratable acidity (TTA), total phenolic content (TPC) and antioxidant activity), rheological (viscosity and flow behaviour), and sensory attributes was scrutinized. Results showed that the pH value decreased by increasing DLS concentration from 1 to 6 %, while the TTA decreased with an increase in DLS from 6 to 9 % (p<0.05). The whey syneresis, firmness and viscosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Our results were in agreement with those obtained by Ivanova, Petkova, Balabanova, Ognyanov, and Vlaseva (), Jridi et al (), and Szwajgier and Gustaw (), who observed the enrichment in total phenolic content and the enhancement of the antioxidant activity of dairy desserts adding with encapsulated cornelian cherry, chokeberry and blackberry juices, date syrup and powder of different Tunisian varieties, and brewery malts, respectively. Amerinasab et al (), Trigueros, Sayas‐Barberá, Pérez‐Álvarez, and Sendra () and Gad, Kholif, and Sayed (), noted the same thing in yogurt based on date liquid sugar, yogurts manufactured with dates blanching water, and yogurt resulting from the combination of date palm syrup and skim milk, respectively. Moreover, many studies have reported the enhancement of the antioxidant power of dairy products supplemented with fruits and vegetables (Felfoul, Borchani, Samet‐Bali, Attia, & Ayadi, ; Kermiche et al, ; Sah, Vasiljevic, McKechnie, & Donkor, ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results were in agreement with those obtained by Ivanova, Petkova, Balabanova, Ognyanov, and Vlaseva (), Jridi et al (), and Szwajgier and Gustaw (), who observed the enrichment in total phenolic content and the enhancement of the antioxidant activity of dairy desserts adding with encapsulated cornelian cherry, chokeberry and blackberry juices, date syrup and powder of different Tunisian varieties, and brewery malts, respectively. Amerinasab et al (), Trigueros, Sayas‐Barberá, Pérez‐Álvarez, and Sendra () and Gad, Kholif, and Sayed (), noted the same thing in yogurt based on date liquid sugar, yogurts manufactured with dates blanching water, and yogurt resulting from the combination of date palm syrup and skim milk, respectively. Moreover, many studies have reported the enhancement of the antioxidant power of dairy products supplemented with fruits and vegetables (Felfoul, Borchani, Samet‐Bali, Attia, & Ayadi, ; Kermiche et al, ; Sah, Vasiljevic, McKechnie, & Donkor, ).…”
Section: Resultsmentioning
confidence: 92%
“…Phenolic compounds were extracted according to the method described by Amerinasab, Labbafi, Mousavi, and Khodaiyan (). The results were expressed as mg gallic acid equivalent (GAE) per 1 g of the dry weight (DW): mg GAE/g DW.…”
Section: Methodsmentioning
confidence: 99%
“…This increment was not significant (P ≤0.05) on 1 st and 4 th day then it was significant (P ≤0.05) on 8 th and 12 th day of storage. The increment of syneresis by progressing storage periods may be attributed to the damage and substantial structural reorganization of the gel network (Amerinasab et al, 2015) because the proteins making a desired texture loss their property and their bond with water is degenerated (Shahbandari et al, 2016). These results are in agreement with those reported by Das et al (2013) who found that the syneresis increased on 12 th day of storage in dahi fortified with colostrum.…”
Section: Whey Syneresismentioning
confidence: 99%
“…Sucrose, fruits and non-nutritive sweeteners such as stevia are the main sweeteners, which are used in the production of flavored yoghurts (43)(44)(45). In dairy desserts, viscosity is one of main effective factors in organoleptic properties.…”
Section: Effect Of Hfcs On Dairy Products' Propertiesmentioning
confidence: 99%